Rom, Italien. Domus Aurea - Beste, Heinz-Jürgen (e-Forschungsberichte des DAI, 2023)
The Rome Department of the German Archaeological Institute was asked by the Soprintendenza Archeologica di Roma, together with the Centro Nazionale di Ricerca, to prepare the extensive documentation needed for the restoration of the Domus Aurea. In Rooms 22–34 the modern cement floor was removed, revealing that all marble slabs had been removed in antiquity. Instead, a wooden floor had been inserted, preventing direct contact with the cold and humid ground and thus enabling the storage of delicate goods, e.g. wheat, fabric and spices.